Plan de comunicación corporativa para la cooperativa de ahorro y crédito Juan Pío de Mora del cantón Quinsaloma año 2015 - Lindao Jiménez, Evelyn Estefania (2016)
A corporate communications plan for the credit union Juan Pio de Mora, Quinsaloma Canton, 2015. It is focused on detailed internal and external communication; based on that three specific objectives according to the steps of the plan breaks down; conduct a situation analysis allowing identification of the background and communication objectives, identify strategies and actions for the implementation of corporate communication plan and set the budget and control means for monitoring the activities. In preparing the introduction of the research it was conducted and the current situation of the problem was known to the respective problematization, systematization of it, besides the general objective and specific is determined. The conceptual framework was developed with more focused information according to the research topic, methods, techniques and primary and secondary sources was determined to proceed to find the results. By analyzing current status it was determined important data such as: history, mission, vision, values, and SWOT which allowed to investigate and identify possible shortcomings in the management of communication that has the cooperative. Strategies and actions that are aimed at achieving effective compliance with each of the objectives established for the purpose of generating profit to the cooperative was determined. Budget and control means which was critical to the development of corporate communication plan as it allowed us to know the amount of $ $ 5.289 is earmarked for the launch was also performed.